Factors Affecting Prospective Students in Choosing Local Private University - admin-bisnisman, admin-bisnisman; Bakar, Abu; Rahmania, Tasya; Heliani, Heliani (Jurnal Bisnisman : Riset Bisnis dan Manajemen, 2020)
The intense competition of the higher education industry in Indonesia has a considerable impact on prospective students choosing Private Universities. With this research, we can determine the main factors affecting prospective students by distributing questionnaires to 950 prospective students of XYZ University as a sample. This study used a quantitative descriptive method with 15 variables grouped into seven factors: product factors, physical evidence factors, price factors, location factors, reference group factors, motivational factors, and personal factors. From these seven factors, the affordable location factor is the most influential factor for prospective students deciding to study at XYZ University.